2015
DOI: 10.1016/j.juro.2015.02.080
|View full text |Cite
|
Sign up to set email alerts
|

Image Guided Focal Therapy for Magnetic Resonance Imaging Visible Prostate Cancer: Defining a 3-Dimensional Treatment Margin Based on Magnetic Resonance Imaging Histology Co-Registration Analysis

Abstract: Purpose We compared prostate tumor boundaries on magnetic resonance imaging and radical prostatectomy histological assessment using detailed software assisted co-registration to define an optimal treatment margin for achieving complete tumor destruction during image guided focal ablation. Materials and Methods Included in study were 33 patients who underwent 3 Tesla magnetic resonance imaging before radical prostatectomy. A radiologist traced lesion borders on magnetic resonance imaging and assigned a suspic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
103
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(115 citation statements)
references
References 28 publications
7
103
1
4
Order By: Relevance
“…Although we have shown that LADA was more accurate in identifying lesions than LDA, there is an obvious requirement to improve the sensitivity of the algorithm before it can be applied in clinical settings. As a margin of up to 9 mm was acceptable and even recommended in focal therapies, 13 we will investigate how adding margins would improve the lesion detection sensitivity. In addition, we will incorporate prior knowledge of the lesions to further optimize the results provided by LADA.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have shown that LADA was more accurate in identifying lesions than LDA, there is an obvious requirement to improve the sensitivity of the algorithm before it can be applied in clinical settings. As a margin of up to 9 mm was acceptable and even recommended in focal therapies, 13 we will investigate how adding margins would improve the lesion detection sensitivity. In addition, we will incorporate prior knowledge of the lesions to further optimize the results provided by LADA.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for the higher recurrence rate if MRI-guided focal therapy is performed may be the underestimation of cancer by the MRI method. Le Nobin et al [19] showed very nicely that a simulated cylindrical treatment volume based only on the MRI boundary missed 14.8% of the tumor volume compared with a simulated cylindrical volume based on the histologic boundary. Therefore, the authors recommend a 9-mm safety margin when planning ablation of MRI-visible lesions.…”
Section: Discussionmentioning
confidence: 99%
“…6.ay kontrolünde rekürens gelişen 2 hastada ise ablasyon alanının tümörü yeterince kapsamadığı görülmüştür. Ablasyon alanı, MRG'de izlenen kitleyi ve en az komşu 9 mm'yi kapsayacak şekilde planlanmalıdır [57].…”
Section: Eği̇ti̇ci̇ Noktaunclassified